A New Method for Estimation of Surfactin - Mubarak, Muhammad Usman; Adnan, Ahmad; Shafiq, Muhammad Imtiaz; Rehman, Abdul; Awan, Javeed A. (Asian Journal of Chemistry, 2015)
Surfactin is a lipopeptide biosurfactant produced by some strains of Bacillus subtilis. Due to its surface tension reducing ability it has a potential application as a drug in certain types of cancer diseases. It has a strong ability to cause hemolysis. In this work the hemolytic activity of surfactin was used for its estimation by measuring released haemoglobin spectrophotometrically. Herein a new method has been developed involving microscopic counting of red blood cells for surfactin estimation. There has been a good agreement between the newly developed microscopic counting of red blood cells and already reported spectrophotometric method.